Application of Traditional Chinese Medicine ointment and nursing management of a patient with bone pain induced by multiple myeloma (中药膏摩治疗1例多发性骨髓瘤所致骨痛患者的护理体会) - BAI Yu (白羽) (中西医结合护理)
This paper summarizes the Traditional Chinese Medicine (TCM) ointment treatment and nursing management of a patient with bone pain induced by multiple myeloma. Nurses had evaluated the degree of bone pain and negative emotion of the patient before taking interventions. Based on the TCM basic theory, the TCM ointment treatment and emotional care were carried to relieve the pain, anxiety and depression, and improve the treatment compliance. (本文总结1例多发性骨髓瘤导致骨痛患者采用中药膏摩治疗的护理体会。护理人员评估患者疼痛负性情绪严重程度, 基于中医基础理论, 开展中药膏摩和情志干预, 有效减轻患者疼痛程度, 缓解焦虑、抑郁情绪, 提高了治疗依从性。)